2010
DOI: 10.1021/jp9104823
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Reaction Mechanisms and Kinetics of Cyanomidyl Radical with NO

Abstract: The mechanisms and kinetics of the reaction of the cyanomidyl radical (HNCN) with the NO have been investigated by the high-level ab initio molecular orbital method in conjunction with VTST and RRKM theory. The species involved have been optimized at the B3LYP/6-311++G(3df,2p) level and their single-point energies are refined by the CCSD(T)/aug-cc-PVQZ//B3LYP/6-311++G(3df,2p) method. Our calculated results indicate that the favorable pathways for the formation of several isomers of an HNCN-NO complex. Formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…To ascertain the computational approaches used in this paper, we calculated geometrical parameters and electron affinities of HNCN radical. Previously, we have computed the N–C–N and N–H bond lengths as well as the ∠CNH bond angle predicted by the hybrid density functional B3LYP method with a modest 6-311++G­(3df,2p) basis set and found them to be 2.46 Å, 1.02 Å, and 113.6°, which are in satisfactory agreement with experimental values (2.470 ± 0.002 Å, 1.034 ± 0.020 Å, and 116.5 ± 2.7°, respectively) . In addition, at the CCSD­(T)/aug-cc-PVQZ//B3LYP/6-311++G­(3df,2p) level, the calculated EA value of HNCN radical is 2.62 eV and agrees satisfactorily with the experimental value, 2.622 ± 0.005 eV .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…To ascertain the computational approaches used in this paper, we calculated geometrical parameters and electron affinities of HNCN radical. Previously, we have computed the N–C–N and N–H bond lengths as well as the ∠CNH bond angle predicted by the hybrid density functional B3LYP method with a modest 6-311++G­(3df,2p) basis set and found them to be 2.46 Å, 1.02 Å, and 113.6°, which are in satisfactory agreement with experimental values (2.470 ± 0.002 Å, 1.034 ± 0.020 Å, and 116.5 ± 2.7°, respectively) . In addition, at the CCSD­(T)/aug-cc-PVQZ//B3LYP/6-311++G­(3df,2p) level, the calculated EA value of HNCN radical is 2.62 eV and agrees satisfactorily with the experimental value, 2.622 ± 0.005 eV .…”
Section: Resultssupporting
confidence: 78%
“…The energies used in the calculation are plotted in Figure , and the vibrational frequencies and moments of inertia are listed in Table S1 of the Supporting Information. The Lennard-Jones (LJ) parameters employed for the RNCN + NO reactions are as follows: for Ar, σ = 3.47 Å and ε/ k = 114.0 K, and for RNCN–NO, σ = 3.90 Å and ε/ k = 205.0 K, which are approximated to be the same as our previous work of the HNCN–NO system . For the variational rate constant calculations by the VariFlex code, a statistical treatment of the transitional-mode contributions to the transition-state partition functions is performed variationally.…”
Section: Resultsmentioning
confidence: 99%
“…In our calculation for N electrons in a system, independent calculations are made for the corresponding ( N − 1), N , and ( N + 1) electron systems with the same geometry. A natural population analysis yields q k ( N − 1), q k ( N ), and q k ( N +1) for the predicted possible sites of reaction of CNN and NO molecules, and the Fukui function is calculated as a difference of populations between N and N + 1 or N and N − 1 electron systems . We choose the f 0 value for comparison since the CNN + NO reaction is more characteristic of a radical system .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the mechanisms and rate parameters for reactions involving nitrogen compounds have been extensively investigated in relation to such air pollutants . In 1975 Lyon reported ammonia to rapidly and nearly quantitatively reduce NO to N 2 and H 2 O if used in the presence of O 2 at temperatures 900−1100 °C. , This chemical process was quickly developed into what is called the thermal DeNO x process. There have been numerous reports on theoretical and experimental approaches to eliminate NO, many of which employ cyanogen species as an effective reagent to remove NO. Our interest has been focused on the non-hydrogenated carbene molecule, diazocarbene (CNN).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some theoretical studies have been reported on the mechanisms of the OH + HNCN, O( 3 P) + HNCN, O 2 + HNCN and NO + HNCN reactions 10–12. However, no kinetic studies have been performed on the reactivity of HNCN toward some important atmospheric species in experiment.…”
Section: Introductionmentioning
confidence: 99%